Family Communication and School Environment as a Cause of Bullying Behavior in Adolescents - Aminah, Ratih Siti; Lubis, Djuara P.; Hastuti, Dwi; Muljono, Pudji (Journal of Family Sciences, 2023)
Communication between adolescents and parents is an important part of the period of self-discovery. Bullying behavior that occurs in adolescents develops from an ongoing process of interaction in the family, school, and peer environment. Teens are especially vulnerable to engaging in bullying behavior. The communication environment of adolescents with parents, schools, and peers is an important factor in the occurrence of bullying behavior. Adolescents will imitate based on the results of observations encountered in family, school, and peers. Communication between adolescents and parents is important in minimizing bullying behavior. This research uses qualitative methods. Research location in Bogor. Data collection was conducted through observation, in-depth interviews, and documentation studies. The study involved five informants consisting of two bullies and three victims of bullying. The research informants selected were young men and women in Bogor, aged 17-18 years, high school students, and equivalent school who had been victims and/or perpetrators of bullying. In the initial stage, researchers distributed an open-ended questionnaire according to the above criteria. This open questionnaire aims to reveal aspects of the adolescent communication environment in the family, school environment, and peers. The results showed that the communication environment in the family, school, and peers of adolescents plays an important role in the occurrence of bullying behavior. Bullying behavior in adolescents begins as a victim and then as a perpetrator or perpetrator becomes a victim. Bullying carried out by adolescent girls at school is verbal and social, while bullying carried out by adolescent boys at school is verbal and physical.